1999
DOI: 10.1074/jbc.274.39.27513
|View full text |Cite
|
Sign up to set email alerts
|

Ligands for κ-Opioid and ORL1 Receptors Identified from a Conformationally Constrained Peptide Combinatorial Library

Abstract: We have screened a synthetic peptide combinatorial library composed of 2 ؋ 10 7 ␤-turn-constrained peptides in binding assays on four structurally related receptors, the human opioid receptors , ␦, and and the opioid receptor-like ORL1. Sixty-six individual peptides were synthesized from the primary screening and tested in the four receptor binding assays. Three peptides composed essentially of unnatural amino acids were found to show high affinity for human -opioid receptor. Investigation of their activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 53 publications
3
71
0
1
Order By: Relevance
“…Buprenorphine, which was widely used as an analgesic molecule in newborns and infants, has also been shown to have ORL1 agonist activity (31). On the other hand, [Nphe 1 ]NC(1-13)NH 2 produces an antinociceptive action and potentiates morphineinduced analgesia (39) and a recent study described a new class of drugs with opioid agonist/ORL1 antagonist activities (53), thus opening new possibilities in the field of neuroprotection and analgesia in neonates.…”
Section: Figurementioning
confidence: 99%
“…Buprenorphine, which was widely used as an analgesic molecule in newborns and infants, has also been shown to have ORL1 agonist activity (31). On the other hand, [Nphe 1 ]NC(1-13)NH 2 produces an antinociceptive action and potentiates morphineinduced analgesia (39) and a recent study described a new class of drugs with opioid agonist/ORL1 antagonist activities (53), thus opening new possibilities in the field of neuroprotection and analgesia in neonates.…”
Section: Figurementioning
confidence: 99%
“…The following NOP ligands are currently available: i) small non peptide molecules, e.g. the agonist Ro 64-6198 [29] and the antagonists J-113397 [46] and SB-612111 [52]; ii) small peptides such as the hexapeptides Ac-RYYRWK-NH 2 and Ac-RYYRIK-NH 2 [19] and the pseudopentadapeptide III-BTD [2]; iii) a large series of N/ OFQ related peptides chemically modified for increasing agonist potency or for reducing or eliminating efficacy. Details about these three classes of NOP ligands can be found in recent review articles such as [53] and [3].…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive activity has been reported for , ␦, and opioid receptors (Costa and Herz, 1989;Becker et al, 1999;Burford et al, 2000) as well as for some opioid receptor mutants (e.g., Huang et al, 2001). In addition, studies have demonstrated that chronic exposure to opioid agonists can increase constitutive signaling activity of , ␦, and opioid receptors (Costa and Herz, 1989;Becker et al, 1999;Liu and Prather, 2001).…”
mentioning
confidence: 98%